Method for preparing lithium iron manganese phosphate positive electrode material by short process of iron manganese ore

CN122916089APending Publication Date: 2026-10-16CENT SOUTH UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202611229081.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-13
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0009]针对现有技术中锰铁分离流程复杂、资源利用率低以及LMFP材料导电性差、结构稳定性不足等瓶颈问题,本发明提供了一种铁锰矿短流程制备磷酸锰铁锂正极材料的方法

Benefits of technology

(1)本发明以铁锰矿为直接原料,经还原浸出获得含Mn、Fe的浸出液,摒弃了传统工艺中Mn、Fe深度分离并分别制备高纯锰盐和高纯铁盐的复杂流程,通过共沉淀法一步构建Mn-Fe无限固溶体前驱体,进而制备磷酸锰铁锂正极材料,真正实现了从矿物资源到正极材料的短流程定向转化,显著缩短了工艺流程并大幅降低了生产成本;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122916089A_ABST
    Figure CN122916089A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of mineral resource comprehensive utilization and lithium ion battery cathode material preparation, and specifically discloses a method for preparing a lithium iron manganese phosphate cathode material from an iron manganese ore through a short process. x Fe 1‑x C2O4 (0.1≤x≤0.9) and then mixing the precursor with a lithium source, a phosphorus source and a carbon source, and obtaining the lithium iron manganese phosphate cathode material through sintering. The method does not require manganese iron deep separation and complex impurity removal, has the advantages of a short process, low cost, high resource utilization rate and green environmental protection, and the obtained lithium iron manganese phosphate cathode material has excellent electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of comprehensive utilization of mineral resources and preparation of lithium-ion battery cathode materials, and particularly to a short-process method for preparing lithium iron phosphate cathode materials from iron-manganese ore. Background Technology

[0002] With the rapid development of new energy vehicles and the energy storage industry, the demand for high-energy-density, high-safety, and low-cost lithium-ion battery cathode materials continues to grow. Lithium manganese iron phosphate (LiMn) x Fe 1-x PO4 (LMFP) combines the high safety of lithium iron phosphate with the high operating voltage brought by manganese, and is considered an important development direction for the next generation of olivine-type lithium-ion battery cathode materials.

[0003] Existing methods for preparing LMFP mainly include high-temperature solid-state methods, hydrothermal methods, sol-gel methods, and co-precipitation methods. While the high-temperature solid-state method is simple and suitable for large-scale production, it suffers from problems such as poor raw material mixing uniformity, high sintering temperature, wide particle size distribution, and easy segregation of manganese and iron elements, making it difficult to achieve a uniform solid solution structure. In contrast, the co-precipitation method can achieve simultaneous precipitation of Mn and Fe ions in a liquid phase environment, resulting in a uniform distribution of manganese and iron elements at the atomic scale, effectively reducing the risk of element segregation and impurity phase formation during subsequent sintering. Furthermore, the co-precipitation method allows for controllable modification of precursor particle size, morphology, and tap density by adjusting parameters such as pH, temperature, feed rate, and stirring rate, which is significant for improving the rate performance and cycle stability of LMFP. Patent CN121735226A discloses a manganese-iron phosphate precursor and its method for preparing lithium-ion battery cathode materials, improving the uniformity of iron and manganese element distribution and cycle performance through precursor regulation. Replacing traditional mechanical mixing with liquid-phase homogeneous mixing has become an important development direction for LMFP preparation.

[0004] Currently, the industrial production of LMFPs mainly relies on high-purity manganese and iron salts as raw materials. However, manganese and iron resources in nature mostly exist in symbiotic or associated forms, such as iron-manganese ore, manganese-rich slag, and various secondary resources containing manganese and iron. Since Mn and Fe have similar ionic radii and chemical properties, obtaining manganese and iron salts that meet the requirements for cathode material preparation from these manganese-iron associated minerals typically requires multiple stages, including leaching, redox regulation, deep impurity removal, and manganese-iron separation. This process faces prominent problems such as difficulties in selectively separating manganese and iron, lengthy process flows, and large amounts of waste liquid and slag, leading to increased environmental burden. Furthermore, the mineral resource processing stage is disconnected from the cathode material preparation stage. In addition, deep separation and purification primarily aims to remove associated elements, often neglecting the potential of some associated components as beneficial doping elements for cathode materials, thus failing to achieve high-value utilization of associated resources. Therefore, how to reduce the deep separation and purification steps of Mn and Fe in the utilization of manganese-containing iron resources, and directly prepare a uniformly composed Mn-Fe precursor from the leachate containing Mn and Fe, and then obtain lithium manganese iron phosphate cathode material, thereby realizing a short-process directional conversion from mineral resources to cathode materials, is a key issue that urgently needs to be addressed in the current technology system.

[0005] To address the aforementioned issues, a few studies have explored routes for directly constructing lithium-ion battery cathode materials from mineral resource leachates or complex systems. For example, patent CN107579218A discloses a method for directly preparing nickel-cobalt-aluminum ternary cathode material precursors from acid leaching solutions of laterite nickel ore. This method obtains the ternary precursor through impurity removal, composition control, and co-precipitation. However, this method still requires multi-stage stepwise impurity removal and selective separation of the leachate, and repeated pH adjustment, precipitation, solid-liquid separation, and acid dissolution steps to obtain a nickel-cobalt-rich solution. The process remains relatively complex and fails to effectively avoid the lengthy process caused by deep separation and purification of complex mineral leachates. Patent CN117185268A discloses a method for preparing lithium iron phosphate / graphene composite cathode material using manganese ore overflow tailings reduction leaching solution. However, this technology is mainly for manganese ore overflow tailings leaching solution with specific composition and fixed Mn / Fe ratio. It has limited adaptability to different iron-manganese ore raw materials with different grades and compositions, and lacks systematic consideration for the synergistic utilization of associated elements in the mineral.

[0006] In summary, how to overcome the bottleneck of selective separation and directional conversion in the direct preparation of LMFP from complex manganese-iron resources, and develop a short-process technology that combines broad raw material adaptability and full utilization of associated elements, remains a core challenge that urgently needs to be addressed in this field.

[0007] In addition, LMFP materials themselves also face challenges such as low electronic conductivity and Mn content. 3+The induced Jahn-Teller effect leads to intrinsic problems such as decreased structural stability. Currently, carbon coating and metal ion doping are common strategies to improve their electrochemical performance. For example, patent CN120288731A discloses a method for preparing lithium manganese iron phosphate cathode material, which utilizes magnesium and boron synergistic doping and a dual-carbon source sintering process to significantly improve the material's electronic conductivity and specific capacity. Although ion doping has become an important way to enhance the performance of LMFPs, existing doping technologies usually require the introduction of high-purity metal salts as doping sources, which not only increases the complexity of the process but also increases production costs. For iron-manganese ores rich in associated elements such as Al, Ca, Cu, and Mg, traditional processing routes often treat these elements as impurities and remove them deeply, failing to fully explore their potential electrochemical modification value and resulting in a waste of associated resources.

[0008] Therefore, developing a short-process green preparation method that uses iron-manganese ore reduction leaching solution as direct raw material, avoids deep separation of manganese and iron and complex impurity removal processes, directly constructs Mn-Fe infinite solid solution precursors through co-precipitation and simultaneously achieves in-situ doping of associated elements, is of great scientific significance and has significant industrial application prospects for reducing LMFP production costs, improving the utilization rate of all components of mineral resources, and promoting the green manufacturing of new energy materials. Summary of the Invention

[0009] To address the bottlenecks in existing technologies, such as complex manganese-iron separation processes, low resource utilization, poor conductivity, and insufficient structural stability of LMFP materials, this invention provides a short-process method for preparing lithium manganese iron phosphate cathode materials from iron-manganese ore.

[0010] Another core objective of this invention is to fully utilize the inherent associated elements such as Cu, Al, and Mg in the leaching solution of iron-manganese ore, allowing them to enter the LMFP lattice in situ during co-precipitation and subsequent high-temperature sintering. This achieves autonomous doping without the need for additional copper, aluminum, or magnesium sources, thereby simultaneously improving the electronic conductivity and interfacial stability of the material. This in-situ doping strategy for associated elements not only eliminates the need for complex deep purification processes and reduces reagent consumption, but also realizes the high-value synergistic utilization of mineral resources.

[0011] It should be noted that the reducing agent and the reducing protectant described in this invention have different stages of action and different functions, and cannot be substituted for each other. Specifically, the reducing agent (such as pyrite, sodium lignosulfonate, etc.) is added in the reduction leaching stage of step S1, and its function is to promote the reduction and dissolution of Mn and Fe components in the iron-manganese ore; the reducing protectant (such as ascorbic acid) is added before the addition of the precipitant in step S2, and its function is to remove residual Fe in the leachate. 3+ Reduced to Fe 2+ And inhibit Fe during subsequent co-precipitation process 2+They are oxidized to maintain suitable Mn and Fe valence states, thus favoring Mn. 2+ and Fe 2+ A uniform Mn-Fe solid solution precursor is formed.

[0012] Furthermore, it should be noted that both pyrite and manganese iron ore are natural mineral mixtures, and their effective component content varies significantly depending on the origin, vein, and batch. In practice, the effective component content in the ore is used as a benchmark, and the ratio of ore to reducing agent is determined by back-calculation after component analysis to ensure that the target leaching effect can be achieved under different batches of raw materials.

[0013] To address the above problems, this invention provides a short-process method for preparing lithium iron phosphate cathode materials from iron-manganese ore, comprising the following steps: S1. After the iron-manganese ore is subjected to reduction leaching and solid-liquid separation in sequence, a leachate containing Mn and Fe elements is obtained; wherein, the leachate containing Mn and Fe elements also contains associated elements, and the associated elements include at least one of Cu, Al, Ca and Mg. S2. Add a precipitant to the leachate containing Mn and Fe elements to carry out a co-precipitation reaction to obtain the Mn-Fe infinite solid solution precursor; S3. The Mn-Fe infinite solid solution precursor is mixed with a lithium source, a phosphorus source and a carbon source, and then sintered to obtain a lithium manganese iron phosphate cathode material; wherein, the associated elements enter the lattice of the lithium manganese iron phosphate cathode material during the sintering process to achieve in-situ doping of the associated elements.

[0014] Preferably, in step S1, the reductive leaching is carried out in an acidic leaching system, wherein the acid used in the acidic system is at least one of sulfuric acid, hydrochloric acid, phosphoric acid, nitric acid, oxalic acid, and citric acid, with a concentration of 0.5~4.0 mol / L; and the reducing agent used in the reductive leaching is at least one of pyrite, sodium lignosulfonate, sodium sulfite, and sodium metabisulfite.

[0015] It should be noted that the reducing agent (such as pyrite, sodium lignosulfonate, etc.) is added in the reduction leaching stage of step (1), and its function is to promote the reduction and dissolution of Mn and Fe components in iron-manganese ore.

[0016] Preferably, in step S1, the particle size of the iron-manganese ore is 50-500 mesh; the liquid-to-solid ratio of the reduction leaching system is 3-20 mL / g, the reaction temperature is 20-120℃, and the reaction time is 10-240 min. Preferably, the reduction leaching is carried out under microwave reactor-assisted conditions. It should be noted that using a microwave reactor to enhance the leaching of iron-manganese ore shortens the reaction time and improves reaction efficiency.

[0017] Preferably, in step S1, when the reducing agent used in the reductive leaching is pyrite, the mass ratio of the effective reducing component in the pyrite to the effective component in the iron-manganese ore is 0.05:1.0 to 0.50:1.0, based on the effective components; wherein, the effective reducing component in the pyrite is FeS2, and the effective components in the iron-manganese ore are compounds of high-valence Mn and high-valence Fe, the high-valence Mn compounds include at least one of MnO2, Mn2O3, MnOOH, and Mn3O4, and the high-valence Fe compounds include at least one of Fe2O3, FeOOH, and Fe3O4; when the reducing agent used in the reductive leaching is sodium lignosulfonate, sodium sulfite, and / or sodium metabisulfite, the amount of the reducing agent added is 5wt% to 50wt% of the iron-manganese ore.

[0018] Preferably, in step S2, the precipitant is at least one selected from oxalic acid, sodium oxalate, ammonium oxalate, potassium oxalate, and lithium oxalate; the Mn-Fe unlimited solid solution precursor is Mn x Fe 1-x C2O4, 0.1≤x≤0.9.

[0019] It should be noted that this invention utilizes oxalate ions as a precipitating agent to precipitate Mn 2+ with Fe 2+ Simultaneous precipitation in a liquid-phase system achieves a uniform solid solution distribution of the two metal elements at the atomic scale, which helps reduce the compositional inhomogeneity caused by elemental segregation in traditional preparation processes. Simultaneously, this infinite solid solution structure effectively alleviates the Jahn-Teller effect in high-manganese systems, improving the material's structural stability. Particularly in subsequent sintering, carbon coating, and in-situ doping processes, it helps improve doping uniformity and reduce interfacial impedance, thereby enhancing the electrochemical performance of the LMFP cathode material.

[0020] More preferably, the precipitant is a mixed solution of oxalic acid and sodium oxalate. It should be noted that ferrous oxalate and manganese oxalate have similar solubility product constants, and both are chemically stable and not easily oxidized by oxygen.

[0021] Preferably, step S2 further includes adding a reducing agent to the leachate, the reducing agent being used to remove residual Fe in the leachate. 3+ Reduced to Fe 2+ And inhibit Fe during subsequent co-precipitation process 2+ The oxidation is used to maintain the divalent state of Mn and Fe ions; the reducing protectant is ascorbic acid.

[0022] Preferably, the pH of the coprecipitation reaction system is 0.5~5.0, the reaction temperature is 10~90℃, the reaction time is 10~240 min, the stirring rate is 100~800 r / min, and the atmosphere is an inert atmosphere.

[0023] It should be noted that the aforementioned inert atmosphere is at least one of nitrogen, helium, and argon.

[0024] Preferably, in step S3, the lithium source is at least one of lithium hydroxide, lithium carbonate, lithium dihydrogen phosphate, lithium acetate, and lithium nitrate; the phosphorus source is at least one of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, phosphoric acid, and lithium dihydrogen phosphate; the carbon source is at least one of glucose, sucrose, citric acid, starch, polyethylene glycol, and polyvinyl alcohol; and the molar ratio of the lithium source, phosphorus source, and the total amount of Mn and Fe in the Mn-Fe infinite solid solution precursor is Li:P:(Mn+Fe)=0.90~1.15:0.90~1.10:1.

[0025] Preferably, in step S3, the sintering process is performed using one-step sintering or two-step sintering; When one-step sintering is used, the sintering steps are as follows: High-temperature sintering is carried out at 350~950℃ for 1~24 h; When a two-step sintering process is used, it includes: (a) Pre-sintering is carried out at 250~600℃ for 1~24 h; (b) The temperature is then raised to 350~950℃ for high-temperature sintering, and the sintering time is 1~24 h; The sintering process is carried out in an inert atmosphere or in an inert atmosphere and a reducing atmosphere; the inert atmosphere is at least one of nitrogen, argon and helium.

[0026] For example, the reducing atmosphere mentioned above includes at least one of hydrogen, carbon monoxide, ammonia, and methane.

[0027] It should be noted that the above sintering process can be achieved by one-step sintering or two-step sintering, but the material obtained by two-step sintering has better properties.

[0028] Based on the same inventive concept, the present invention also provides a lithium-ion battery, comprising lithium manganese iron phosphate material prepared by any of the above preparation methods as the positive electrode active material.

[0029] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) This invention uses iron-manganese ore as a direct raw material and obtains a leachate containing Mn and Fe through reduction leaching. It abandons the complicated process of deep separation of Mn and Fe and preparation of high-purity manganese salt and high-purity iron salt in traditional process. It constructs Mn-Fe infinite solid solution precursor in one step through co-precipitation method, and then prepares lithium manganese iron phosphate cathode material. It truly realizes the short-process directional conversion from mineral resources to cathode material, significantly shortens the process and greatly reduces the production cost. (2) By adjusting the Mn / Fe ratio and co-precipitation process parameters, the present invention enables Mn and Fe to co-precipitate in the form of oxalate solid solution precursors, ensuring the high uniformity of element distribution at the molecular scale, effectively shortening the ion diffusion distance in the subsequent high-temperature solid-phase reaction, promoting the efficient synthesis of pure phase LMFP, which is beneficial to reducing energy consumption and suppressing the generation of impurity phases. (3) The highly uniform precursor prepared by the present invention and the conductive network formed by subsequent carbon coating produce a synergistic effect, which can significantly improve the interfacial charge transfer characteristics and electrochemical reaction kinetics of the electrode material, reduce electrochemical polarization, and thus effectively improve the specific capacity and long-cycle stability of the material. (4) This invention makes full use of the Cu, Al, Mg and other elements associated in iron-manganese ore, so that they enter the lithium manganese phosphate lattice or grain boundary in situ during leaching, co-precipitation and high-temperature sintering, without the need to add high-purity copper salt, aluminum salt, magnesium salt and other doping reagents. It transforms the impurity elements that need to be deeply removed in traditional processes into functional doping components in situ, and realizes the high-value synergistic utilization of mineral associated resources. (5) This invention can effectively regulate the local electronic structure and lattice environment of the material by synergistic in-situ doping of associated elements such as Cu, Al, and Mg, thereby enhancing electron transport capability and suppressing Mn. 3+ The induced Jahn-Teller distortion improves the stability of the crystal structure, thereby enhancing the rate performance and cycle life of the cathode material; (6) This invention significantly reduces the lengthy processes of deep separation, purification, and removal of associated elements of manganese and iron, effectively reducing the consumption of chemical reagents such as acids and alkalis, and reducing the amount of waste liquid and waste residue generated from the source, thus significantly reducing the environmental burden. By synergistically utilizing the main elements Mn and Fe with associated elements such as Cu, Al, and Mg, it balances process economy and environmental friendliness, making it easy to promote and apply in industry. Attached Figure Description

[0030] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0031] Figure 1 The image shows the XRD pattern of an iron-manganese ore deposit in Hunan Province used in Embodiment 1 of this invention. Figure 2 The image shows the XRD pattern of a pyrite deposit in Shandong Province used in Embodiment 1 of this invention. Figure 3 The image shows the XRD pattern of the Mn-Fe infinite solid solution prepared in Example 1 of this invention. Figure 4 This is a SEM image of the Mn-Fe infinite solid solution prepared in Example 1 of this invention; Figure 5 This is a SEM image of the manganese iron oxalate precursor prepared in Comparative Example 1 of this invention. Figure 6 The image shows the XRD pattern of the lithium manganese iron phosphate cathode material (LMFP) finally prepared in Example 1 of this invention. Figure 7 The image shows a SEM image of the lithium manganese iron phosphate cathode material (LMFP) finally prepared in Example 1 of this invention. Figure 8 The image shows a SEM image of the lithium manganese iron phosphate cathode material (LMFP) finally prepared in Comparative Example 1 of this invention. Figure 9 The graph shows the cycle performance of button batteries assembled with lithium manganese iron phosphate cathode materials finally obtained in Embodiment 1, Comparative Example 1 and Comparative Example 3 of the present invention after 150 cycles at 1 C. Figure 10 The graph shows the rate performance of button batteries assembled from lithium manganese iron phosphate cathode materials finally obtained in Examples 1, 1, and 3 of this invention. Detailed Implementation

[0032] To make the present invention easier to understand, specific embodiments are described below to further illustrate the invention. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Unless otherwise defined, the technical terms used below have the same meaning as understood by those skilled in the art; unless otherwise specified, the raw materials and reagents involved herein can be purchased commercially or prepared by known methods.

[0033] To address the bottlenecks in existing technologies, such as complex manganese-iron separation processes, low resource utilization, poor conductivity, and insufficient structural stability of LMFP materials, this invention provides a short-process method for preparing lithium manganese iron phosphate cathode materials from iron-manganese ore.

[0034] The following examples and comparative models further illustrate this point.

[0035] The iron-manganese ore used in the following embodiments of the present invention comes from a certain place in Hunan Province, and the pyrite comes from a certain place in Shandong Province. The main elements and contents of the ore are shown in Table 1 and Table 2.

[0036] Table 1. Main elements and contents of a manganese mine in a subway station in Hunan Province

[0037] Table 2. Main elements and contents of pyrite in a certain area of ​​Shandong Province

[0038] It should be noted that both pyrite and manganese iron ore are natural mineral mixtures, and their effective component content varies significantly depending on the origin, vein, and batch. The ore-to-reducing agent mass ratios in the following examples are all determined by back-calculation after component analysis, based on the effective component content, to ensure that the target leaching effect can be achieved under different batches of raw materials. Those skilled in the art can adjust the feeding ratio by equivalent conversion based on the actual ore grade and the effective component content.

[0039] Example 1 A method for preparing lithium iron phosphate cathode material from iron-manganese ore using a short process includes the following steps: (1) Reduction leaching of iron-manganese ore and pyrite Leaching was enhanced using an MCR-3 atmospheric pressure microwave chemical reactor with a microwave power of 800 W. 0.75 g of pyrite (200 mesh) and 5 g of manganese ore were weighed and added with 2 mol / L sulfuric acid at a liquid-to-solid ratio of 8 mL / g. Leaching was carried out at 60℃ for 45 min, and the leachate and leaching residue were obtained by filtration.

[0040] The leachate was tested and found to contain 9.82 g / L of Mn and 9.30 g / L of Fe, with leaching rates of 92.73% and 80.00% for Mn and Fe, respectively. The mass of the leachate residue was 2.37 g.

[0041] X-ray diffraction (XRD) analysis was performed on the aforementioned iron-manganese ore and pyrite, and the results are shown in the figure. Figure 1 and Figure 2 As shown. Figure 1 As shown, the XRD pattern of the iron-manganese ore mainly detects characteristic diffraction peaks of MnO2, FeO(OH), and SiO2, indicating that the raw material is mainly composed of manganese-bearing phases, iron-bearing phases, and siliceous gangue minerals. Figure 2 As shown, the XRD pattern of pyrite mainly detects the characteristic diffraction peak of FeS2, with a small amount of diffraction peaks of AlFe3 and SiO2, indicating that FeS2 is the main phase of the pyrite, while containing a small amount of Al-containing phase and SiO2 impurity phase.

[0042] (2) Preparation of Mn-Fe Infinite Solid Solution Ascorbic acid was added to the leachate obtained in step (1) as a reducing protectant to remove residual Fe from the leachate. 3+ Reduced to Fe 2+ And inhibit Fe during subsequent co-precipitation process 2+ The oxidation process is used to maintain the divalent state of Mn and Fe ions. Nitrogen gas is first bubbled into deionized water to remove dissolved oxygen, and a certain amount of A mol / L mixed solution of oxalic acid and sodium oxalate is prepared (A = c(H₂C₂O₄) + c(C₂O₄)). 2- )=1), add the mixed solution of oxalic acid and sodium oxalate dropwise to the leachate, the reaction temperature is 60℃ and the stirring rate is 300 r / min. Then add 18% ammonia solution to the reaction system to adjust the pH to 1~2. After the precipitate is formed, continue stirring in a 60℃ water bath for 60 min. Nitrogen gas is continuously introduced into the entire reaction system.

[0043] After the reaction was completed, the reaction system was sealed and aged at room temperature for 12 h. The prepared pale yellow precipitate was washed until the pH of the filtrate was ≈7, and then vacuum dried at 60 °C for several hours to obtain Mn-Fe unlimited solid solution powder (i.e., manganese iron oxalate precursor).

[0044] The Mn-Fe unlimited solid solution powder was found to contain 16.89% Mn and 12.60% Fe, with a Mn / Fe molar ratio of 0.58:0.42.

[0045] XRD and SEM images of Mn-Fe infinite solid solution are shown below. Figure 3 and Figure 4 As shown. Figure 3 As shown, the observed peaks match very well with the XRD peaks of typical monoclinic α-oxalate phases. No obvious impurity peaks were found, indicating that a high-purity manganese iron oxalate dihydrate precursor was synthesized via co-precipitation. The intensity of the diffraction peaks suggests that the synthesized precursor material has excellent crystallinity. Figure 4 As shown, the synthesized precursor is cubic in shape, with particle size in the micrometer range, and exhibits a certain degree of aggregation and stacking. The particles are relatively dense overall, with obvious crystal faces and edges, and some particles have a small number of fine particles attached to their surface.

[0046] (3) Preparation of LMFP cathode material 1. Take 2 g of the Mn-Fe indefinite solid solution powder described in step (3), add lithium hydroxide, ammonium dihydrogen phosphate and glucose of 10% of the total mass of raw materials according to Li:(Mn+Fe):P=1.05:1:1, add 15 mL of acetone as a dispersant, and the ball-to-material ratio is 10:1. Place them together in a 50 mL zirconia ball mill jar and place them in a planetary ball mill at 800 r / min for 2.5 h each in forward and reverse directions to obtain a uniformly mixed material.

[0047] 2. After drying the uniformly mixed material, place it in a tube furnace and pre-sinter at 400℃ for 2 h at a heating rate of 5℃ / min. Then, calcine it at 700℃ for 8 h to obtain lithium manganese iron phosphate cathode material (LMFP).

[0048] The XRD and SEM results of the lithium manganese iron phosphate (LMFP) cathode material prepared above are shown in Figure 1. Figure 6 and Figure 7 As shown. Figure 6 As shown, the positions and intensities of all diffraction peaks in the material are consistent with the standard card PDF#42-0580. No characteristic peaks associated with graphitized carbon were observed in the figure, indicating that the carbon component exists in an amorphous form; no diffraction peaks corresponding to impurities were detected, confirming the solid solution distribution of Mn, Fe, and Cu atoms within the lattice, indicating that the typical olivine structure is preserved after Cu doping. Figure 7 As shown, the lithium manganese iron phosphate cathode material prepared using the iron-manganese ore-pyrite leaching system is mainly composed of fine particles. The particles are irregularly shaped and exhibit a certain degree of agglomeration. The primary particles are relatively small in size and uniformly distributed, with some porosity between them. The overall morphology is relatively loose, which is beneficial for increasing the contact area between the active material and the electrolyte and shortening the Li-P leaching time. + Diffusion pathway.

[0049] Example 2 The difference between this embodiment and Embodiment 1 is that the order of adding the oxalic acid and sodium oxalate mixed solution and the leachate in step (2) is reversed (i.e., in this embodiment, the leachate is added dropwise to the oxalic acid and sodium oxalate mixed solution). Other operations and parameters are the same as in Embodiment 1.

[0050] The Mn-Fe unlimited solid solution powder was found to contain 18.06% Mn and 10.82% Fe, with a Mn / Fe molar ratio of 0.63:0.37.

[0051] Example 3 The difference between this embodiment and Embodiment 1 is that step (1) is different. Step (1) specifically involves weighing 5 g of 200-mesh iron-manganese ore and 1 g of sodium lignin sulfonate, adding sulfuric acid with a concentration of 2 mol / L at a liquid-to-solid ratio of 8 mL / g, leaching at 90°C for 30 min, and filtering to obtain the leachate and leach residue. Other steps and parameters are the same as in Embodiment 1.

[0052] The leachate was tested and found to contain 9.63 g / L of Mn and 7.35 g / L of Fe, with leaching rates of 90.96% and 86.00%, respectively, and a leaching residue mass of 2.51 g. The Mn and Fe contents in the Mn-Fe unlimited solid solution were 17.27% and 12.34%, respectively, with a Mn / Fe molar ratio of 0.59:0.41.

[0053] Example 4 The difference between this embodiment and embodiment 3 is that the order of adding the oxalic acid and sodium oxalate mixed solution and the leachate in step (2) is reversed (i.e., in this embodiment, the leachate is added dropwise to the oxalic acid and sodium oxalate mixed solution). Other operations and parameters are the same as in embodiment 3.

[0054] The Mn and Fe contents in the Mn-Fe unlimited solid solution were found to be 19.48% and 10.18%, respectively, with a Mn / Fe molar ratio of 0.66:0.34.

[0055] Example 5 The difference between this embodiment and Embodiment 1 is that the two-step sintering in step (3) is replaced with a one-step sintering (the one-step sintering specifically refers to heating to 700℃ and calcining for 10 h at a heating rate of 5℃ / min). Other operations and parameters are the same as in Embodiment 1.

[0056] Comparative Example 1 The difference between this comparative example and Example 1 is that in step (1), MnSO4·H2O and FeSO4·7H2O were weighed according to the same Mn / Fe molar ratio to prepare a mixed salt solution. Other operations and parameters are the same as in Example 1.

[0057] The manganese iron oxalate precursor prepared in this comparative example was analyzed by SEM, and the results are as follows: Figure 5 As shown. By Figure 5 As can be seen, the precursor synthesized in this comparative example is approximately cubic in shape, with individual particles measuring approximately 3-8 μm in size, and exhibits an aggregated and stacked state. The overall material structure is relatively dense, with a smooth surface, and is composed of solid blocky crystals rather than sheet-like stacks. SEM analysis of the LMFP cathode material prepared in this comparative example yields the following results: Figure 8 As shown. By Figure 8It can be seen that the lithium manganese iron phosphate cathode material prepared by mixed salt solution also exhibits obvious particle agglomeration, but the particle size distribution is relatively wide, and large irregular block or plate-like particles can be observed in some areas. The overall morphology uniformity is relatively poor, and the agglomeration degree is more obvious in some areas.

[0058] Comparative Example 2 The difference between this comparative example and Example 2 is that in step (1), MnSO4·H2O and FeSO4·7H2O were weighed according to the same Mn / Fe molar ratio to prepare a mixed salt solution. Other operations and parameters are the same as in Example 2.

[0059] Comparative Example 3 The difference between this comparative example and Example 1 is that in step (1), MnSO4·H2O, FeSO4·7H2O and CuSO4·5H2O were weighed according to the same Mn / Fe / Cu molar ratio to prepare a mixed salt solution. Other operations and parameters are the same as in Example 1.

[0060] Performance testing and results analysis The manganese iron oxalate precursors prepared in Examples 1-5 and Comparative Examples 1-3 were digested with aqua regia, and their elemental contents (mg / L) were compared. The experimental results are shown in Table 3.

[0061] Table 3 Comparison of elemental contents of ferromanganate precursors in Examples 1-5 and Comparative Examples 1-3

[0062] As shown in Table 3, the oxalate coprecipitation method can achieve the desired Mn content. 2+ with Fe 2+ The synergistic precipitation of oxalic acid forms an Mn-Fe infinite solid solution precursor. The extremely low levels of impurities such as Al, Ca, and Mg indicate that the oxalic acid system exhibits high selectivity for Mn and Fe, effectively enriching manganese and iron elements and removing impurities from natural iron-manganese ores. The low Cu content, with higher levels in the precursors of Examples 1-2 compared to Examples 3-4, is attributed to the use of pyrite as a reducing agent. Compared to the chemically pure reagent system, the precursor composition obtained from the natural mineral source system is similar, demonstrating the feasibility of this process for directly preparing LMFP precursors using low-cost mineral sources.

[0063] The physicochemical properties of the manganese iron oxalate precursors prepared in Examples 1-5 and Comparative Examples 1-3 were compared, and the results are shown in Table 4.

[0064] Table 4 Comparison of physicochemical properties of manganese oxalate precursors in Examples 1-5 and Comparative Examples 1-3

[0065] As shown in Table 4, the Mn / Fe molar ratio in the obtained precursor is close to the target ratio (6:4), indicating that this method has good controllability over the ferromanganese composition. Different addition methods affect the Mn / Fe ratio. Adding the leachate to the oxalic acid system results in more significant Mn enrichment and an increased Mn / Fe ratio. Adding the oxalic acid system to the leachate produces a better particle size distribution and more dispersed crystals in the co-precipitated product. Furthermore, using sodium lignosulfonate as a reducing agent changes the precursor morphology from a single cubic shape to a coexistence of rod-shaped and cubic shapes, indicating its ability to regulate crystal growth behavior. The precursor obtained from the natural mineral source system has properties similar to those of the chemically pure reagent system, further demonstrating that this method is suitable for the direct preparation of LMFP precursors from low-cost mineral sources.

[0066] The positive electrode materials prepared in Examples 1-5 and Comparative Examples 1-3 were weighed with conductive carbon (Super-P) and polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1. PVDF was pre-dissolved in N-methyl-2-pyrrolidone (NMP) to prepare a 5 wt% PVDF / NMP solution. Then, 650-700 mL of NMP was added as a dispersion medium. Zirconia beads with a diameter of 5 mm were added and the mixture was ball-milled in a planetary ball mill at 400 r / min for 2 h until the slurry was fully mixed and had optimal fluidity. (2) The uniformly prepared slurry was coated onto carbon-coated aluminum foil to a thickness of 150 µm, and then dried in a vacuum drying oven at 60 °C for 12 h. The dried electrodes were then stamped into discs with a diameter of 12 mm, ensuring that the areal density of each electrode was approximately 2 mg / cm³. 2 In an argon-filled glove box, CR2016 button half-cells were assembled using lithium foil as the counter electrode, Celgard 2500 membrane as the separator, and a dedicated LMFP electrolyte (model LB-878, DoDoChem). (3) The batteries prepared above were subjected to electrochemical tests on a LAND BT2000 battery testing system. Constant current charge-discharge tests were conducted at a constant temperature of 28°C, a standard current density of 170 mAh / g, and a voltage window of 2.0–4.5 V. After activation at 0.1 C for three cycles, the batteries were cycled at 1 C for extended periods. Rate performance tests were performed at 0.1 C, 0.2 C, 0.3 C, 0.5 C, 1 C, 3 C, 5.0 C, and 0.1 C, with five cycles at each rate. Specific results are shown in Table 5.

[0067] Table 5. Performance comparison of lithium manganese iron phosphate cathode materials in Examples 1-5 and Comparative Examples 1-3

[0068] Table 5 shows that the LMFP cathode material prepared by the two-step sintering process exhibits excellent rate performance and cycle stability. Example 1 demonstrates the best overall performance, with discharge specific capacities of 119.79 mAh / g and 106.71 mAh / g at 0.1 C and 5 C, respectively, and a capacity retention of 92.57% after 150 cycles. In contrast, the rate performance of the material in Example 5 decreased significantly after omitting the pre-sintering step, indicating that pre-sintering is beneficial for improving the crystal structure and carbon coating uniformity. Furthermore, the high-rate performance of the material decreased with increasing Mn content, indicating that an excessively high Mn ratio increases polarization and reduces Li... + Diffusion kinetics. In Example 3, after 150 cycles, the capacity retention further increased to 96.92%, indicating that the rod-shaped structure helps alleviate structural stress during cycling. Meanwhile, Example 1 used pyrite as a reducing agent, and compared to Example 3, the precursor had a higher Cu content, achieving in-situ doping during calcination. The introduction of Cu ions helps improve the material's electronic conductivity, reduce charge transfer impedance, thereby improving the material's rate performance and having a positive effect on the stability of the voltage plateau during charge and discharge. Figure 9 and Figure 10 As shown, the cycling performance and rate performance of Example 1 and Comparative Example 3 are both superior to those of Comparative Example 1, demonstrating that Cu doping can be used to regulate the structure and electrochemical performance of lithium manganese iron phosphate cathode materials. Compared with Example 1, Comparative Example 3 uses a mixed salt solution of MnSO4·H2O, FeSO4·7H2O, and CuSO4·5H2O as raw material, and its 0.1 C and 5 C discharge specific capacities are 120.77 mAh / g and 104.98 mAh / g, respectively. After 150 cycles, the capacity retention rate is 92.67%, which is similar to the overall performance of Example 1. Among them, the 5C discharge specific capacity of Example 1 is slightly higher than that of Comparative Example 3, indicating that by using iron manganese ore-pyrite leaching solution as raw material and utilizing the associated Cu element for in-situ introduction, electrochemical performance comparable to that of a high-purity Mn, Fe, Cu salt formulation system can still be obtained without the need for additional copper-containing compounds, and it also exhibits good high-rate performance. This demonstrates that the present invention can achieve the synergistic utilization of Mn, Fe and associated Cu elements in minerals while reducing the need for deep separation and purification of Mn and Fe and the addition of exogenous Cu.

[0069] In summary, this invention provides a method for preparing lithium manganese iron phosphate cathode materials based on natural iron-manganese ore. This method achieves efficient leaching of Mn and Fe elements through a sulfuric acid system, and uses oxalate co-precipitation to prepare an Mn-Fe infinite solid solution precursor, effectively avoiding the problems of difficult separation of manganese and iron elements, component segregation, and uneven mixing in traditional processes. By controlling the oxalic acid system, the dropping method, and reaction conditions, the Mn / Fe ratio can be controlled and adjusted, resulting in a uniform precursor structure. Simultaneously, Cu elements associated with the ore source are in-situ doped during material preparation, which helps improve the material's electronic conductivity and structural stability; oxalic acid co-precipitation has high selectivity for impurity elements such as Al, Ca, and Mg, enabling effective enrichment and purification of manganese and iron elements. Furthermore, this invention employs a two-step sintering process to prepare the lithium manganese iron phosphate cathode material. The pre-sintering process facilitates the slow decomposition of the precursor, uniform carbon layer coating, and stable crystal structure formation, thereby significantly improving the material's rate performance and cycle stability. The results show that this invention provides a simple, efficient, and industrially promising method for the direct preparation of high-performance lithium manganese iron phosphate cathode materials from low-cost mineral sources.

[0070] The above embodiments merely illustrate several implementation methods of this application, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent application. It should be noted that those skilled in the art can make various modifications and improvements without departing from the inventive concept of this application, and these all fall within the protection scope of this application. Therefore, the protection scope of this patent application should be determined by the appended claims.

Claims

1. A method for preparing lithium iron phosphate cathode material from iron-manganese ore using a short-process method, characterized in that, Includes the following steps: S1. After the iron-manganese ore is subjected to reduction leaching and solid-liquid separation in sequence, a leachate containing Mn and Fe elements is obtained; wherein, the leachate containing Mn and Fe elements also contains associated elements, and the associated elements include at least one of Cu, Al, Ca and Mg. S2. Add a precipitant to the leachate containing Mn and Fe elements to carry out a co-precipitation reaction to obtain the Mn-Fe infinite solid solution precursor; S3. The Mn-Fe infinite solid solution precursor is mixed with a lithium source, a phosphorus source and a carbon source, and then sintered to obtain a lithium manganese iron phosphate cathode material; wherein, the associated elements enter the lattice of the lithium manganese iron phosphate cathode material during the sintering process to achieve in-situ doping of the associated elements.

2. The method for preparing lithium iron phosphate cathode material from iron-manganese ore using a short-process method according to claim 1, characterized in that, In step S1, the reduction leaching is carried out in an acidic leaching system. The acid used in the acidic system is at least one of sulfuric acid, hydrochloric acid, phosphoric acid, nitric acid, oxalic acid, and citric acid, with a concentration of 0.5~4.0 mol / L. The reducing agent used in the reduction leaching is at least one of pyrite, sodium lignosulfonate, sodium sulfite, and sodium metabisulfite.

3. The method for preparing lithium iron phosphate cathode material from iron-manganese ore using a short process according to claim 2, characterized in that, In step S1, the particle size of the iron-manganese ore is 50-500 mesh; the liquid-to-solid ratio of the reduction leaching system is 3-20 mL / g, the reaction temperature is 20-120℃, and the reaction time is 10-240 min; the reduction leaching is carried out under the auxiliary conditions of a microwave reactor.

4. The method for preparing lithium iron phosphate cathode material from iron-manganese ore using a short-process method according to claim 2, characterized in that, In step S1, when the reducing agent used in the reductive leaching is pyrite, the mass ratio of the effective reducing component in the pyrite to the effective component in the iron-manganese ore is 0.05:1.0 to 0.50:1.0, based on the effective components. The effective reducing component in the pyrite is FeS2, and the effective components in the iron-manganese ore are compounds of high-valence Mn and high-valence Fe. The high-valence Mn compounds include at least one of MnO2, Mn2O3, MnOOH, and Mn3O4, and the high-valence Fe compounds include at least one of Fe2O3, FeOOH, and Fe3O4. When the reducing agent used in the reductive leaching is sodium lignosulfonate, sodium sulfite, and / or sodium metabisulfite, the amount of the reducing agent added is 5wt% to 50wt% of the iron-manganese ore.

5. The method for preparing lithium iron phosphate cathode material from iron-manganese ore using a short-process method according to claim 1, characterized in that, In step S2, the precipitant is at least one selected from oxalic acid, sodium oxalate, ammonium oxalate, potassium oxalate, and lithium oxalate, and the Mn-Fe unlimited solid solution precursor is Mn x Fe 1-x C2O4, 0.1≤x≤0.

9.

6. The method for preparing lithium iron phosphate cathode material from iron-manganese ore using a short-process method according to claim 1, characterized in that, Step S2 further includes adding a reducing agent to the leachate, the reducing agent being used to remove residual Fe in the leachate. 3+ Reduced to Fe 2+ And inhibit Fe during subsequent co-precipitation process 2+ The oxidation is used to maintain the divalent state of Mn and Fe ions; the reducing protectant is ascorbic acid.

7. The method for preparing lithium iron phosphate cathode material from iron-manganese ore using a short-process method according to claim 1, characterized in that, The reaction system for the coprecipitation reaction has a pH of 0.5 to 5.0, a reaction temperature of 10 to 90°C, a reaction time of 10 to 240 min, a stirring rate of 100 to 800 r / min, and an inert atmosphere.

8. The method for preparing lithium iron phosphate cathode material from iron-manganese ore using a short-process method according to claim 1, characterized in that, In step S3, the lithium source is at least one of lithium hydroxide, lithium carbonate, lithium dihydrogen phosphate, lithium acetate, and lithium nitrate; the phosphorus source is at least one of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, phosphoric acid, and lithium dihydrogen phosphate; the carbon source is at least one of glucose, sucrose, citric acid, starch, polyethylene glycol, and polyvinyl alcohol; and the molar ratio of the lithium source, phosphorus source, and the total amount of Mn and Fe in the Mn-Fe infinite solid solution precursor is 0.90~1.15:0.90~1.10:

1.

9. The method for preparing lithium iron phosphate cathode material from iron-manganese ore using a short-process method according to claim 1, characterized in that, In step S3, the sintering process can be performed in one step or two steps. When one-step sintering is used, the sintering steps are as follows: High-temperature sintering is carried out at 350~950℃ for 1~24 h; When a two-step sintering process is used, it includes: (a) Pre-sintering is carried out at 250~600℃ for 1~24 h; (b) The temperature is then raised to 350~950℃ for high-temperature sintering, and the sintering time is 1~24 h; The sintering process is carried out in an inert atmosphere or in an inert atmosphere and a reducing atmosphere; the inert atmosphere is at least one of nitrogen, argon and helium.

10. A lithium-ion battery, characterized in that, The lithium manganese iron phosphate material prepared by the preparation method according to any one of claims 1 to 9 is used as the positive electrode active material.

Citation Information

Patent Citations

  • Method for directly preparing nickel-cobalt-aluminum ternary cathode material precursor by using acid leaching solution of laterite nickel ore

    CN107579218A

  • Method for preparing lithium iron manganese phosphate / graphene positive electrode material from manganese ore overflow tailing reduction leachate and application of lithium iron manganese phosphate / graphene positive electrode material

    CN117185268A

  • Preparation method of lithium manganese iron phosphate positive electrode material and lithium manganese iron phosphate positive electrode material

    CN120288731A

  • Ferromanganese phosphate precursor and method for preparing lithium ion battery positive electrode material by using same

    CN121735226A